Muslim Investor Psychology and Decision-Making in Islamic Stock Investment - baharsyah, akmal ilham; Imron Mawardi (Universitas Airlangga, 2024)
This study aims to determine and identify the psychological factors of Muslim investors in their decision making to invest in Islamic stocks. The questionnaire was distributed online and received 121 respondents. The research approach used is a quantitative approach with structural equation model-partial least square (SEM-PLS) analysis technique. The data that has been collected is processed using the SmartPLS version 3.0 application. The findings of this study indicate that the variables of familiarity bias and herding behavior have a positive and significant influence on investment decisions by Muslim investors in investing in Islamic stocks. While the variable conservatism bias does not have a significant influence on investment decisions by Muslim investors in investing in Islamic stocks. The implication of this research is that it helps to provide an overview of information regarding psychological factors on investors to be better in the future in investing in Islamic stocks. So that they can take steps and make decisions appropriately and wisely in investing in Islamic stocks in the Islamic capital market